针轮销孔展成技术 - 崔正昀 (Jixie chuandong)
Pinhole machining of pin gear housing is one of important procedures in manufacturing cycloid speed reducer. Because structure of the housing is like an internal gear with semi-circular tooth grooves, it can be machined by method of generating. This paper introduces the generating method and presents equation, characteristics, some design considerations and manufacturing method of tooth profile of the cutter. The method has been used in production and evident economic benefits have been gained in China.